High-Risk Factors Affecting Adolescent Reproductive Health - Susanti, Santi; Lisnawati, Lilis (Genius Journal, 2024)
Introduction: Adolescent reproductive health services consist of activities aimed at maintaining the reproductive health of adolescents. According to data from the Central Statistics Agency (BPS), Bappenas, and UNFPA in 2010, 63 million adolescents in Indonesia are vulnerable to unhealthy behaviors. Data from adolescent posyandu visits reveal that the majority of adolescents suffer from anemia, malnutrition, or overnutrition, including obesity. However, the specific risk behaviors affecting the reproductive health of adolescents in Cikunir Village remain unknown. Objective: This study aims to identify the risk factors affecting the reproductive health of adolescents in Cikunir Village. Method: This research employed a descriptive method. The study population comprised all adolescents in Cikunir Village. A total of 201 adolescents were selected as samples using purposive sampling. Secondary data were sourced from the reproductive health survey conducted as part of the Village Development and Empowerment Grant Program (PHP2D) by the Ministry of Education and Culture of the Republic of Indonesia in 2021. Data were analyzed using univariate analysis. Results: The study identified several risk factors for adolescent reproductive health: 11.4% of adolescents smoked, 1% had tried drugs, and 15.9% had watched pornographic videos. Additionally, 29.4% of adolescents reported having boyfriends or girlfriends, and 23.4% were influenced by a social environment associated with risky behaviors. Conclusion: Adolescent reproductive health in Cikunir Village is affected by various risk factors, including smoking, drug use, exposure to pornography, and risky social environments. Parents are advised to provide attention and affection to their children, monitor their social and school environments, and actively engage in guiding them towards healthier behaviors.